Periaqueductal gray calcitonin gene-related peptide modulates trigeminovascular neurons. (December 2015) - Pozo-Rosich, P; Storer, RJ; Charbit, AR; Goadsby, PJ
Background: Calcitonin gene-related peptide (CGRP) receptor antagonism is an approach to migraine therapy. The locus of action of antimigraine treatment is not resolved. The objective was to investigate CGRP receptors in the ventrolateral periaqueductal gray (vlPAG) involved in the modulation of trigeminovascular nociception by descending influences on neurotransmission. Methods: The presence of calcitonin receptor-like receptor (CLR) and receptor activity modifying protein 1 (RAMP1), which form functional CGRP receptors, was investigated. CGRP and its receptor antagonists, olcegepant and CGRP (8 –37 ), were microinjected into the vlPAG while changes of neural responses in the trigeminocervical complex (TCC) were monitored. Results: Immunoreactivity indicated the presence of functional CGRP receptor components in the vlPAG and adjacent mesencephalic trigeminal nucleus. Inhibition of TCC responses to stimulation of dural afferents and ophthalmic cutaneous receptive fields after microinjection of bicuculline into vlPAG indicated a connection between the vlPAG and TCC neurons. CGRP facilitated these TCC responses, whereas olcegepant and CGRP (8 –37 ) decreased them. Conclusions: CGRP and its receptor antagonists act on neurons in the region of vlPAG to influence nociceptive transmission in the TCC. This suggests CGRP receptor antagonists may act at loci outside of the TCC and reinforces the concept of migraine as a disorder of the brain.